Comparison of experimentally and theoretically determined radiation characteristics of photosynthetic microorganisms. (May 2016) - Kandilian, Razmig; Pruvost, Jérémy; Artu, Arnaud; Lemasson, Camille; Legrand, Jack; Pilon, Laurent
Abstract: This paper aims to experimentally and directly validate a recent theoretical method for predicting the radiation characteristics of photosynthetic microorganisms. Such predictions would facilitate light transfer analysis in photobioreactors (PBRs) to control their operation and to maximize their production of biofuel and other high-value products. The state of the art experimental method can be applied to microorganisms of any shape and inherently accounts for their non-spherical and heterogeneous nature. On the other hand, the theoretical method treats the microorganisms as polydisperse homogeneous spheres with some effective optical properties. The absorption index is expressed as the weighted sum of the pigment mass absorption cross-sections and the refractive index is estimated based on the subtractive Kramers–Kronig relationship given an anchor refractive index and wavelength. Here, particular attention was paid to green microalgae Chlamydomonas reinhardtii grown under nitrogen-replete and nitrogen-limited conditions and to Chlorella vulgaris grown under nitrogen-replete conditions. First, relatively good agreement was found between the two methods for determining the mass absorption and scattering cross-sections and the asymmetry factor of both nitrogen-replete and nitrogen-limited C. reinhardtii with the proper anchor point. However, the homogeneous sphere approximation significantly overestimated the absorption cross-section of C. vulgaris cells. The latter were instead modeled as polydisperse coated spheres consisting of an absorbing core containing pigments and a non-absorbing but strongly refracting wall made of sporopollenin. The coated sphere approximation gave good predictions of the experimentally measured integral radiation characteristics of C. vulgaris . In both cases, the homogeneous and coated sphere approximations predicted resonance in the scattering phase function that were not observed experimentally. However, these approximations were sufficiently accurate to predict the fluence rate and local rate of photon absorption in PBRs. Abstract : Highlights: The radiation characteristics of microalgae were determined theoretically and experimentally. The experimental method relied on nephelometer and transmittance measurements at low cell density. The theoretical method used Lorenz-Mie theory for homogeneous spheres with effective optical properties. Both methods gave similar results for C. reinhardtii under replete and N-limited conditions. C. vulgaris had to be modeled as coated spheres to account for its refracting cell wall.